If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 85 + -79 = 27y + -33y Combine like terms: 85 + -79 = 6 6 = 27y + -33y Combine like terms: 27y + -33y = -6y 6 = -6y Solving 6 = -6y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '6y' to each side of the equation. 6 + 6y = -6y + 6y Combine like terms: -6y + 6y = 0 6 + 6y = 0 Add '-6' to each side of the equation. 6 + -6 + 6y = 0 + -6 Combine like terms: 6 + -6 = 0 0 + 6y = 0 + -6 6y = 0 + -6 Combine like terms: 0 + -6 = -6 6y = -6 Divide each side by '6'. y = -1 Simplifying y = -1
| -n=5 | | x-6=34+34+3x | | x-6=34+34 | | -s=9 | | 2.3=x-5.9 | | x-6=34+x | | 39=z+51 | | 2d=5d-60 | | 5x+(-4)=36 | | 2D=0 | | -11=z-4 | | -2x-45=34+56 | | 4x-3+2x=8x-3-x | | -4(2p+4)-40=2(4p+4) | | -33+5y+3=2(4y-2)-2 | | 5(c-3)=6(c-5) | | x+.0875x=10 | | -5x-1=12 | | 2n-21=-28+3n | | 3x+16xy+16y= | | 5p-5=-41+p | | 8(4k-4)=-54k-32 | | 5x^2-2=9x | | -9=19(h-3) | | 4=0.2(r-0.08) | | x+.0875x=9 | | 5x+3-2x=-15 | | 6(x-4x)= | | 6z+4=z-2 | | 2n-1-3n=5n-7-3n | | 0.2t+.833=.666-t | | -.555x+.333=.222 |